Pathophysiological conditions induced by SARS-CoV-2 infection reduce ACE2 expression in the lung - Miura, Yoko; Ohkubo, Hirotsugu; Nakano, Akiko; Bourke, Jane E.; Kanazawa, Satoshi (Frontiers in Immunology, 2022)
SARS-CoV-2 infection causes a variety of physiological responses in the lung, and understanding how the expression of SARS-CoV-2 receptor, angiotensin-converting enzyme 2 (ACE2), and its proteolytic activator, transmembrane serine protease 2 (TMPRSS2), are affected in patients with underlying disease such as interstitial pneumonia will be important in considering COVID-19 progression. We examined the expression of ACE2 and TMPRSS2 in an induced usual interstitial pneumonia (iUIP) mouse model and patients with IPF as well as the changes in whole-lung ACE2 and TMPRSS2 expression under physiological conditions caused by viral infection. Histopathological and biochemical characteristics were analyzed using human specimens from patients with IPF and precision-cut lung slices (PCLS) from iUIP mouse model showing UIP with honeycombing and severe fibrosis after non-specific interstitial pneumonia. ACE2 expression decreased with acute lung inflammation and increased in the abnormal lung epithelium of the iUIP mouse model. ACE2 is also expressed in metaplastic epithelial cells. Poly(I:C), interferons, and cytokines associated with fibrosis decreased ACE2 expression in PCLS in the iUIP model. Hypoxia also decreases ACE2 via HIF1α in PCLS. Antifibrotic agent, nintedanib attenuates ACE2 expression in invasive epithelial cells. Patients with IPF are at a higher risk of SARS-CoV-2 infection due to the high expression of ACE2. However, ACE2 and TMPRSS2 expression is decreased by immune intermediaries, including interferons and cytokines that are associated with viral infection and upon administration of antifibrotic agents, suggesting that most of the viral infection-induced pathophysiological responses aid the development of resistance against SARS-CoV-2 infection.